Influence of ozone recovery and greenhouse gas increases on Southern Hemisphere circulation - Karpechko, A; Gillett, N; Gray, L; Dall'Amico, M (Journal of Geophysical Research, 2016)
Stratospheric ozone depletion has significantly influenced the tropospheric circulation and climate of the Southern Hemisphere (SH) over recent decades, the largest trends being detected in summer. These circulation changes include acceleration of the extratropical tropospheric westerly jet on its poleward side and lowered Antarctic sea level pressure. It is therefore expected that ozone changes will continue to influence climate during the 21st century when ozone recovery is expected. Here we use two contrasting future ozone projections from two chemistry-climate models (CCMs) to force 21st century simulations of the HadGEM1 coupled atmosphere-ocean model, along with A1B greenhouse gas (GHG) concentrations, and study the simulated response in the SH circulation. According to several studies, HadGEM1 simulates present tropospheric climate better than the majority of other available models. When forced by the larger ozone recovery trends, HadGEM1 simulates significant deceleration of the tropospheric jet on its poleward side in the upper troposphere in summer, but the trends in the lower troposphere are not significant. In the simulations with the smaller ozone recovery trends the zonal mean zonal wind trends are not significant throughout the troposphere. The response of the SH circulation to GHG concentration increases in HadGEM1 includes an increase in poleward eddy heat flux in the stratosphere and positive sea level pressure trends in southeastern Pacific. The HadGEM1-simulated zonal wind trends are considerably smaller than the trends simulated by the CCMs, both in the stratosphere and in the troposphere, despite the fact that the zonal mean ozone trends are the same between these simulations. © Copyright 2010 by the American Geophysical Union.